Kinetics of Desorption of Water and Absorption of Salt During Blanching of Prawn - D.R., Choudhury; R., Chakraborty (Fishery Technology, 2025)
During blanching prawn desorbs water, absorbs sodium chloride from the surrounding blanching solution and undergoes denaturation. The rate of desorption from the muscle tissue was directly proportional to time, temperature and concentration of NaCl in blanching brine and the kinetics of desorption followed the first order reaction. Variation in the concentration of NaCl in the blanching liquor did not alter the mechanism of desorption. The bonding reaction involving ions was disfavoured at high temperature so that the rate constant became independent of ionic strength.